Observational study of pimecrolimus 1% cream for prevention of transcutaneous sensitization in children with atopic dermatitis during their first year of life - Murashkin, Nikolay N.; Namazova-Baranova, Leyla S.; Makarova, Svetlana G.; Ivanov, Roman A.; Grigorev, Stepan G.; Fedorov, Dmitri V.; Ambarchian, Eduard T.; Epishev, Roman V.; Materikin, Alexander I.; Opryatin, Leonid A.; Savelova, Alena A. (Frontiers in Pediatrics, 2023)
Introduction Epidermal barrier dysfunction in children with atopic dermatitis can cause transcutaneous sensitization to allergens and allergic diseases. We evaluated the effectiveness of an early-intervention algorithm for atopic dermatitis treatment, utilizing pimecrolimus for long-term maintenance therapy, in reducing transcutaneous sensitization in infants. Method This was a single-center cohort observational study that enrolled children aged 1-4 months with family history of allergic diseases, moderate-to-severe atopic dermatitis, and sensitization to ≥ 1 of the investigated allergens. Patients who sought medical attention at atopic dermatitis onset (within 10 days) were group 1 “baseline therapy with topical glucocorticoids with subsequent transition to pimecrolimus as maintenance therapy”; patients who sought medical attention later were group 2 “baseline and maintenance therapy with topical glucocorticoids, without subsequent use of pimecrolimus”. Sensitization class and level of allergen-specific immunoglobulin E were determined at baseline, and 6 and 12 months of age. Atopic dermatitis severity was evaluated using the Eczema Area and Severity Index score at baseline and 6, 9 and 12 months of age. Results Fifty-six and 52 patients were enrolled in groups 1 and 2, respectively. Compared with group 2, group 1 demonstrated a lower level of sensitization to cow's milk protein, egg white and house dust mite allergen at 6 and 12 months of age, and a more pronounced decrease in atopic dermatitis severity at 6, 9 and 12 months of age. No adverse events occurred. Discussion The pimecrolimus-containing algorithm was effective in treating atopic dermatitis and prophylaxis of early forms of allergic diseases in infants. Trial registration https://clinicaltrials.gov/NCT04900948, retrospectively registered, 25 May 2021.